Factors affecting the rates of adherence to surveillance recommendations for incidental pancreatic cystic lesions in a large urban safety net hospital. Issue 1 (13th July 2020) - Canakis, Andrew; Maoz, Asaf; Tkacz, Jaroslaw N; Huang, Christopher
Abstract : Background: Pancreatic cystic lesions (PCLs) are a heterogenous group of lesions with varying degrees of malignant potential. PCLs are often incidentally detected on imaging. Management for patients without an immediate indication for resection or tissue sampling entails radiographic surveillance to assess for features concerning for malignant transformation. This study aims to determine the rates of adherence to surveillance recommendations for incidental PCLs, and identify factors associated with adherence or loss of follow-up. Methods: We conducted a single-centre retrospective study of patients at a tertiary safety net hospital with incidentally discovered asymptomatic PCLs. Follow-up was defined as having undergone repeat imaging as recommended in the radiology report. Data were analysed using logistic regression. Results: Within our cohort (n=172), 123 (71.5%) subjects completed follow-up imaging. Attending a gastroenterology appointment was most strongly associated with completing follow-up for PCLs and remained significant (p=0.001) in a multivariate logistic regression model. Subjects without a documented primary care provider were less likely to have follow-up (p=0.028). Larger cyst size was associated with completion of follow-up in univariate only (p=0.067). Conclusion: We found that follow-up of an incidentally discovered PCLs was completed in the majority of our subjects. Incomplete follow-up for PCLs occurred in up to one in three to four patients in our cohort. Access to primary care and utilisation of subspecialty gastroenterology care are associated with completion of follow-up for PCLs. If validated, our findings can guide potential interventions to improve follow-up rates for PCLs.